Improvement Of Mathematics Learning Outcomes About Flat Building Area Through Stad-Type Cooperative Learning Methods For Grade III Students Of SD Negeri 005 Kepenuhan - Juniar Juniar (STKIP Rokania Pasir Pangaraian, 2023)
The formulation of the problem in this study is Whether the STAD-type cooperative learning method can improve mathematics learning outcomes about flat building area in grade 3 semester 2 students of SDN 005 Kepenuhan 2021/2022?